第51次日本南極地域観測隊気象部門報告2010 - 佐々木, 利; ササキ, サトシ; 松元, 誠; マツモト, マコト; 田中, 悦子; タナカ, エツコ; 塩水流, 洋樹; シオズル, ヒロキ; 高見, 英治; タカミ, ヒデハル; Sasaki, Satoshi; Matsumoto, Makoto; et al. (2015)
P(論文) この報告は，第51次日本南極地域観測隊気象部門が，2010 年2月1日から2011年1月31日まで昭和基地において行った気象観測結果をまとめたものである．オゾンゾンデ観測はKC 型オゾンセンサからECC 型オゾンセンサへ2010年4月に移行し，地上オゾン濃度観測は観測機器等の更新を2010年1月に行った．他の観測は観測方法・測器・統計方法等は第50次隊とほぼ同様である． 越冬期間中の特記事項は次のとおりである． 1）2011年1月の月間日照時間159.9時間は，1月として少ない方の極値を更新した． 2）9月5日の日最高気温－1.1℃は，9月としての日最高気温の極値を更新した． 3）昭和基地上空の対流圏において，月平均気温は5-6月にかけて平年より低く推移した．また，下部成層圏では，8月から2011年1月にかけて平年より低く推移した． 4）昭和基地上空のオゾン全量は，9月中旬から12月上旬までオゾンホールの目安となる値をほぼ継続して下回り，10月6日に2010年の最小値である145m atm-cm を記録した．オゾンホール面積の最大値は1990年以降3番目に小さく，オゾン欠損量の最大値は1990年以降4番目に小さかった． This report presents meteorological observations obtained by the Meteorological Observation Team of the 51st Japanese Antarctic Research Expedition (JARE-51) at Syowa Station, Antarctica during February 2010-January 2011. The observation methods, instruments and statistical methods used by JARE-51 were similar to those used by JARE-50, except that the sensor for the ozone sonde observations was changed from KC-type ozone sensor to an ECC-type ozone sensor in April 2010, and the instruments used for surface ozone concentration monitoring were replaced in January 2010. Notable observations recorded by JARE-51 include the following: 1) The monthly sunshine duration in January 2011 was only 159.9 hours, a record low for this month. 2) On 5 September 2010, the daily high temperature was －1.1℃, a record high for the month of September. 3) Tropospheric temperatures during May and June over Syowa Station were lower than normal, and temperatures in the lower stratosphere during August-January were lower than normal. 4) Total ozone over Syowa Station was ＜220 m atm-cm between the mid September and the beginning December. The minimum value in 2010 was 145 m atm-cm. The maximum area of the ozone hole was the third smallest since 1990, and the maximum ozone deficit was the fourth smallest since 1990. Errata | http://id.nii.ac.jp/1291/00010938/ departmental bulletin paper